Prolyl-hydroxylase inhibitor-induced regeneration of alveolar bone and soft tissue in a mouse model of periodontitis through metabolic reprogramming - Zebrowitz, Elan; Aslanukov, Azamat; Kajikawa, Tetsuhiro; Bedelbaeva, Kamila; Bollinger, Sam; Zhang, Yong; Sarfatti, David; Cheng, Jing; Messersmith, Phillip B.; Hajishengallis, George; Heber-Katz, Ellen (Frontiers in Dental Medicine, 2022)
Bone injuries and fractures reliably heal through a process of regeneration with restoration to original structure and function when the gap between adjacent sides of a fracture site is small. However, when there is significant volumetric loss of bone, bone regeneration usually does not occur. In the present studies, we explore a particular case of volumetric bone loss in a mouse model of human periodontal disease (PD) in which alveolar bone surrounding teeth is permanently lost and not replaced. This model employs the placement of a ligature around the upper second molar for 10 days leading to inflammation and bone breakdown and closely replicates the bacterially induced inflammatory etiology of human PD to induce bone degeneration. After ligature removal, mice are treated with a timed-release formulation of a small molecule inhibitor of prolylhydroxylases (PHDi; 1,4-DPCA) previously shown to induce epimorphic regeneration of soft tissue in non-regenerating mice. This PHDi induces high expression of HIF-1α and is able to shift the metabolic state from OXPHOS to aerobic glycolysis, an energetic state used by stem cells and embryonic tissue. This regenerative response was completely blocked by siHIF1a. In these studies, we show that timed-release 1,4-DPCA rapidly and completely restores PD-affected bone and soft tissue with normal anatomic fidelity and with increased stem cell markers due to site-specific stem cell migration and/or de-differentiation of local tissue, periodontal ligament (PDL) cell proliferation, and increased vascularization. In-vitro studies using gingival tissue show that 1,4-DPCA indeed induces de-differentiation and the expression of stem cell markers but does not exclude the role of migrating stem cells. Evidence of metabolic reprogramming is seen by the expression of not only HIF-1α, its gene targets, and resultant de-differentiation markers but also the metabolic genes Glut-1, Gapdh, Pdk1, Pgk1 and Ldh-a in the periodontal tissue.